Medically assisted procreation in times of COVID-19: what impact on health care system organization and the reproductive rights of couples? - Rallo, Giuseppe; Negro, Francesca; Consalvo, Francesca; Piersanti, Valeria; Marinelli, Susanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The emergency caused by the spread of COVID-19 has overwhelmed health care facilities and required the reorganization of health systems in many nations worldwide. A year after its appearance, measures aimed at further containing disease transmission through massive vaccination campaigns. In pregnancy, vaccination should be administered with caution, in light of the lack of reliable data, since pregnant women have been excluded from experimentation. The pandemic has had a significant impact on assisted reproduction procedures in Italy. Methods: The authors have set out to analyze the measures issued by the Italian government in order to counter the spread of COVID-19, in addition to the national and international guidelines on assisted reproduction. Discussion: The purpose of these documents is precautionary in nature: such measures are based on the principles of responsibility and solidarity, essential to stave off the saturation of health systems, curb contagion, but also to lay out a set of rules to starting a pregnancy while preserving the health of couples, operators and newborns. The authors also expound upon the rights claimed by couples seeking access to MAP (i.e. the right to become a parent, the couple’s right to health, interest in demographic development). Conclusions: The coronavirus disease 2019 (COVID-19) has had a major impact on infertile couples. Since the pandemic broke out, Italy, like most European countries, has interrupted most ordinary activities of the centers operating in the field of assisted fertilization. We believe that access to assisted fertilization techniques by sterile and infertile couples should be part of the right to health rather than of the supposed right to become parents or the increase in the birth rate, also evoked as the COVID-19 pandemic unfolded. The current system of compensation and reimbursements needs to be reconfigured in order to prevent any form of discrimination.